ANALISIS PEMROGRAMAN RUANG PADA ASRAMA MAHASISWA UNIVERSITAS TARUMANAGARA - Isnan, Abdul Salam; Choandi, Mieke (Jurusan Arsitektur dan Perencanaan, 2025)
The increasing number of university students in urban areas, particularly in Jakarta, has led to a growing demand for safe, comfortable, and affordable temporary housing. As one of the major private universities in West Jakarta, Tarumanagara University faces the challenge of providing dormitory facilities that are not only functional but also support students’ academic and social activities. This research aims to analyze spatial programming in the design of a student dormitory that responds to its urban context and incorporates the principles of sustainable architecture. The study adopts a descriptive qualitative approach supported by quantitative data through site observation and questionnaires distributed to active students of Tarumanagara University. The findings indicate that students require living spaces that support personal comfort, study activities, and social interaction. The dormitory design includes three room types based on occupancy (1, 2, and 4 persons) and integrates communal facilities such as reading rooms, discussion areas, pantries, sports facilities, and green open spaces. Sustainable design strategies are applied through cross ventilation, natural lighting, environmentally friendly local materials, as well as rainwater harvesting and solar energy systems. Biophilic design elements and communal terraces are incorporated to enhance social interaction and support mental well-being. In conclusion, effective spatial programming serves as the foundation for designing vertical dormitories that are responsive to urban challenges while improving students’ quality of life in terms of functionality, social connectivity, and environmental sustainability. Keywords: sustainable architecture; student dormitory; vertical housing Abstrak Penelitian ini membahas pemrograman ruang pada perancangan asrama mahasiswa Universitas Tarumanagara sebagai respons terhadap meningkatnya kebutuhan hunian di kawasan urban dengan keterbatasan lahan. Tujuan utama dari proyek ini adalah menciptakan hunian vertikal yang tidak hanya memenuhi kebutuhan dasar mahasiswa, tetapi juga mengintegrasikan prinsip arsitektur berkelanjutan. Metode penelitian yang digunakan adalah kualitatif deskriptif, didukung data kuantitatif yang diperoleh melalui observasi lapangan dan penyebaran kuesioner kepada mahasiswa aktif. Hasil penelitian menunjukkan bahwa mahasiswa membutuhkan ruang pribadi yang nyaman, fasilitas belajar yang mendukung, serta ruang komunal yang mendorong interaksi sosial. Berdasarkan analisis tersebut, dirancang tiga tipe kamar: tunggal (3×4 m), ganda (4×6 m), dan bersama empat orang (4×6 m dengan ranjang tingkat), yang secara total mampu menampung hingga 1.568 mahasiswa. Desain bangunan mengusung pendekatan vertikal dengan pemisahan gender antar tower, serta integrasi zona sirkulasi dan ruang bersama seperti ruang baca, diskusi, teras hijau, dan area olahraga. Strategi keberlanjutan diterapkan melalui ventilasi silang, pencahayaan alami, penggunaan energi surya, dan pemanfaatan air hujan. Material lokal dan daur ulang juga digunakan untuk menekan dampak lingkungan. Kesimpulannya, pemrograman ruang yang tepat mampu menghasilkan desain asrama yang adaptif, fungsional, dan mendukung gaya hidup berkelanjutan di lingkungan kampus urban.